Road repair material and application thereof - HE WEILI; HAN XIANFU; YI DAMING (2017)
The invention discloses a road repair material and an application thereof. The road repair material comprises the following components in terms of the total weight of the road repair material: 30 to 60% of tailings, 20 to 40% of cement, 5 to 30% of modified gum and 5 to 20% of polypropylene fiber. The road repair material provided by the invention has the advantages of high strength and good crack resistance. 公开了种道路修补材料及其应用，所述道路修补材料包含尾矿、水泥、改性胶和聚丙烯纤维，其中基于该道路修补材料的总重量计，尾矿的含量为30-60％，水泥的含量为20-40％，改性胶的含量为5-30％，聚丙烯纤维的含量为5-20％。所述道路修补材料兼具有强度高和抗龟裂性好的优点。